The Quranic Exegesis, Reformism, and Women in Twentieth Century Indonesia - Ismail, Norbani B. (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2017)
The paper examines the process of idea formation and intellectual roots of al-ManÄr reform in the field of tafsÄ«r and the transmission of its ideas through the tafsÄ«r work of Haji Abdul Malik Karim Amrullah, also known as Hamka (d.1981). It argues that Hamka internalized al-ManÄr reform in his writings, particularly in his seminal exegetical work, Tafsir al-Azhar. This paper studies Hamkaâ€™s interpretation of the Qurâ€™anic verses and passages related to women, such as: equality in marriage and divorce, gender equality, polygamy, and modesty. Hamka exhibited originality and creativity within a Southeast Asian context in interpreting these verses related to womenâ€™s issues. His writing also synthesized and manifested the symbiotic links between past exegetical approaches and modern ones. The result was an interpretation of the Quran that speaks to the Southeast Asian indigenous Muslim culture, while being firmly rooted within the Islamic intellectual tradition and modernist reform.DOI:Â 10.15408/sdi.v24i3.5187